Anaerobic co-digestion of vegetable waste and swine wastewater in high-rate horizontal reactors with fixed bed - Silva Mazareli, Raissa Cristina da [UNESP] (2016)
Considering the high waste generation that comes from agriculture and livestock farming, as well as the demand for natural gas, it is necessary to develop sustainable technologies which can reduce environmental impact. There is no available literature on the use of high-rate horizontal anaerobic reactors with fixed bed (HARFB) and continuous feed for the co-digestion of vegetable wastes (VW) and swine wastewater (SW). The aim of this work was to evaluate the reactor performance in terms of methane production, organic matter consumption, and removal of total and thermotolerant coliforms under different proportions of SW and VW, and organic loading rates (OLR) of 4.0, 5.2 and 11.0 g COD (L d)(-1). The mixture of SW and VW in the proportions of 90:10, 80:20 and 70:30 (SW:VW) with those OLRs provided great buffering capacity, with partial alkalinity reaching 3552 mg L-1 thereby avoiding the inhibition of methane production by volatile fatty acids produced during the fermentation process. Higher proportions of VW and higher OLR improved volumetric methane production with a maximum value of 1.08 L CH4 (L d)(-1), organic matter removal rates up to 98% and total and thermotolerant coliform removal rates of 99% were also observed. (C) 2016 Elsevier Ltd. All rights reserved.